Building Wellbeing in People With Chronic Conditions: A Qualitative Evaluation of an 8-Week Positive Psychotherapy Intervention for People Living With an Acquired Brain Injury - Tulip, Chloe; Fisher, Zoe; Bankhead, Helen; Wilkie, Lowri; Pridmore, Julia; Gracey, Fergus; Tree, Jeremy; Kemp, Andrew H. (Frontiers in Psychology, 2020)
Research indicates that Acquired Brain Injury (ABI) is associated with significant and chronic impairment across multiple areas of functioning including physical, cognitive, emotional and behavioural domains. Whilst impairments associated with ABI can be ameliorated, cure is seldom possible. The emergence of positive psychology reflects a paradigm shift in health and wellbeing research, highlighting the role of character strengths, positive emotions, meaning, and resilience. Positive psychology interventions have been demonstrated to improve wellbeing in a variety of populations, although research investigating the impact of positive psychotherapy for people living with ABI are sparse. Here we characterize the experience of an 8-week positive psychotherapy intervention for 13 people living with ABI including four mentors and nine participants using thematic analysis of transcripts collected during mini-groups and one-to-one interviews. Six main themes were identified including empowerment, social opportunity, coping, cultivation of positive emotion, consolidation of skills and barriers. Results indicated that wellbeing can be promoted and improved in individuals with ABI. Recent theoretical developments in wellbeing science highlight scope to improve the intervention by connecting individuals to their communities and spending time in nature.